State, Social Interest Housing and Real Estate in Mexico - Merchand Rojas, Marco Antonio; Universidad de Guadalajara (Editorial Pontificia Universidad Javeriana, 2007)
The objective of this paper is to analyze how the Mexican State, from the beginning of the 1990s until the middle of 2016, has applied the bases of the neoliberal model by means of reforms in housing policies aimed at privatizing rural-urban lands. In order to carry out this implementation, the State abandons its active-controller role in the building of social interest housing and transfers this commitment to the real estate developers and the construction industry. This article uses the theoretical and conceptual approach called neoliberal model to explain the reasons why the State implements a neoliberal policy in favor of real estate capitals and to what extent the State has operated as an intermediary, based on extra-economic coercion or land/spaces expropriation -expulsion- and occupation to ensure the profitability of real estate capital. We conclude that the effect of this neoliberal model has not been fulfilled by real estate developers, since they have not offered houses that meet the minimum habitable requirements (they use very poor quality materials and their constructions do not exceed 60 m2). Additionally, most of these housing complexes lack shopping malls, schools, cultural centers, and entertainment venues, making them large dormitories, isolated from the city.